2010
DOI: 10.2169/internalmedicine.49.2929
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized Changes in Serum Vascular Endothelial Growth Factor during the Clinical Course of Chronic Systemic Capillary Leak Syndrome

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…In agreement with individual case reports, our patients had elevated serum VEGF levels at the onset of an acute SCLS episode compared with their baseline, and in one patient VEGF returned to baseline rapidly on presentation with a severe hypotensive crisis. 10,22 Our results show that a short interval of elevated VEGF (and possibly other permeability factors) may exist in SCLS. , and anti-VEGF (bevacizumab) or equivalent concentrations of control IgG (for anti-Ang2 and bevacizumab) or BSA (for IVIG) against episodic sera from 4 to 6 patients was evaluated in the TEER assay.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In agreement with individual case reports, our patients had elevated serum VEGF levels at the onset of an acute SCLS episode compared with their baseline, and in one patient VEGF returned to baseline rapidly on presentation with a severe hypotensive crisis. 10,22 Our results show that a short interval of elevated VEGF (and possibly other permeability factors) may exist in SCLS. , and anti-VEGF (bevacizumab) or equivalent concentrations of control IgG (for anti-Ang2 and bevacizumab) or BSA (for IVIG) against episodic sera from 4 to 6 patients was evaluated in the TEER assay.…”
Section: Discussionmentioning
confidence: 63%
“…20,21 A recent case report found acutely elevated serum VEGF in one patient with SCLS experiencing active symptoms, which correlated with the clinical course. 22 In our series of 20 patients with classic acute SCLS, serum VEGF and Ang2 levels were significantly elevated in the SCLS group during acute episodes compared with asymptomatic SCLS patients and healthy controls (Figure 5A-B). Notably, serum Ang2 was also elevated in patients with SCLS during asymptomatic periods relative to the control group (Figure 5B), which may render them more susceptible to vascular leakage.…”
Section: Elevated Vegf and Ang2 Levels In Sclsmentioning
confidence: 71%
“…Vascular endothelial growth factor (VEGF) is involved in endothelial homeostasis and permeability and there is evidence of a relationship between serum VEGF and the clinical course of SCLS 3. In this respect, SCLS has similarities to the POEMS syndrome (polyneuropathy, organomegaly, endocrinopathy, myeloma and skin abnormalities) which is mediated through VEGF and is associated with plasma cell disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of complements, kinins, prostaglandin, coagulation factors, histamine and serotonin are usually normal in patients with SCLS. Activation of the 5-lipoxygenase pathway and a role for IL-2, VEGF and interferon-ÎČ has been suggested (9)(10)(11)(12). It has also been reported that SCLS occurs after infusions of IL-2, IL-4, tumor necrosis factor, granulocyte-macrophage colony-stimulating factor (GM-CSF) and granulocyte colony-stimulating factor (G-CSF) as well as after autologous and allogeneic stem cell transplantation (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%